Environmental Economy of India - Meena, Kanhaiya Lal (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
One of the key environmental problems facing India is that of particle pollution from the combustion of fossil fuels. This has serious health consequences and with the rapid growth in the economy these impacts are increasing. At the same time, economic growth is an imperative and policy makers are concerned about the possibility that pollution reduction measures could reduce growth significantly. Here are the tradeoffs involved in controlling local pollutants such as particles. Using an established Computable General Equilibrium model, it evaluates the impacts of a tax on coal or on emissions of particles such that these instruments result in emission levels that are respectively 10 percent and 30 percent lower than they otherwise would be in 2030. The main findings are as follows: (i) A 10 percent particulate emission reduction results in a lower gross domestic product but the size of the reduction is modest; (ii) losses in gross domestic product from the tax are partly offset by the health gains from lower particle emissions; (iii) the taxes reduce emissions of carbon dioxide by about 590 million tons in 2030 in the case of the 10 percent reduction and 830 million tons in the case of the 30 percent reduction; and (iv) taken together, the carbon dioxide reduction and the health benefits are greater than the loss of gross domestic product in both cases.